Perancangan Website Sistem Informasi Ticket Reporting - Sudarsono Aritonang; Fajrin Nurhakim; Aziz Wisnu Wardana; Yogo Dwi Prasetyo (STMIK Budi Darma, 2023)
The regional apparatus organization that carries out tourism affairs in Kebumen is the Tourism and Culture Office, which manages nine tourist objects in Kebumen. Reporting of revenue results in the form of ticket sales from each tourist attraction to the Kebumen Tourism and Culture Office is still done manually so it often results in reporting errors. Based on the following problems, innovation is needed to facilitate control and reporting of tourist attraction ticket sales. Therefore, this research creates a Ticket Reporting Information System website. The aim is to facilitate the control of tourist attraction ticket reports at the Kebumen Tourism and Culture Office. The design of this Ticket Reporting Website uses the Waterfall method which consists of analysis, design, coding and testing as well as entity relationship diagrams in designing the database. From the test results using Blackbox testing with 5 modules tested including when logging in whether it is appropriate or not in accordance with the username and password, then Drop Stock, Ticket Sales Reports and Ticket Stock Reports. The result is that all output from the system can run and is in accordance with what is expected. With this website-based information system, you can control directly anywhere without having to visit each tourist attraction in the form of daily ticket sales reports along with income money and at the same time you can see the drop stock of tickets in each tourist attraction